2023
DOI: 10.1029/2022jb025022
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Spectral Estimates of Stress Drop for Small to Moderate Earthquakes With Heterogeneous Slip Distribution: Examples From the 2016–2017 Amatrice Earthquake Sequence

Abstract: Estimates of spectral stress drop are fundamental to understanding the factors controlling earthquake rupture and high frequency ground motion, but are known to include large, poorly‐constrained uncertainties. We use earthquakes from the 2016–2017 sequence in the Italian Appenines (largest event at Norcia, Mw 6.3) to investigate these uncertainties and their causes. The similarly‐sized events near Amatrice (Mw 6.0) and Visso (Mw 5.9) enable better constrained relative analysis. We calculate S wave source spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 81 publications
(256 reference statements)
0
1
0
Order By: Relevance
“…The deconvolution process of the target event by an EGF automatically removes path and site effects without the need for a velocity model to synthesize Green's functions. Although the EGF offers several advantages, its use presents certain difficulties, and selecting an appropriate EGF can be difficult, even when working with an extensive database (Calderoni and Abercrombie, 2023). Focal mechanisms are often not available for small earthquakes, and numerous studies have shown that even for small earthquakes, the effect of directivity cannot be neglected when selecting an EGF (Abercrombie, 2015;Calderoni et al, 2015;Calderoni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The deconvolution process of the target event by an EGF automatically removes path and site effects without the need for a velocity model to synthesize Green's functions. Although the EGF offers several advantages, its use presents certain difficulties, and selecting an appropriate EGF can be difficult, even when working with an extensive database (Calderoni and Abercrombie, 2023). Focal mechanisms are often not available for small earthquakes, and numerous studies have shown that even for small earthquakes, the effect of directivity cannot be neglected when selecting an EGF (Abercrombie, 2015;Calderoni et al, 2015;Calderoni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%